The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1038/ncpendmet1039
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Cushing syndrome due to an ectopic pituitary adenoma

Abstract: The cyclic nature of Cushing syndrome was suggested by the absence of hypercortisolemia during inferior petrosal sinus sampling, and was confirmed by multiple 24 h urine free cortisol measurements. The patient underwent transsphenoidal surgery, during which a 5 mm firm, round, midline sphenoid sinus lesion was identified and resected. In preoperative imaging studies, this lesion had been interpreted as being a mucosal polyp. At microscopic examination, the lesion was found to be a pituitary adenoma, which stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Cyclical secretion of ACTH in EAS has been described in association with typical bronchial and malignant carcinoid tumour of the lung, gastric carcinoid, oncocytic carcinoid of the kidney, bronchial adenoma, phaeochromocytoma, ectopic pituitary adenoma and in occult tumours [48,69,[82][83][84]. A recent review reported a prevalence of 26% of EAS in patients with cyclic Cushing's syndrome from published series and case reports [83].…”
Section: Specific Considerations In Easmentioning
confidence: 95%
“…Cyclical secretion of ACTH in EAS has been described in association with typical bronchial and malignant carcinoid tumour of the lung, gastric carcinoid, oncocytic carcinoid of the kidney, bronchial adenoma, phaeochromocytoma, ectopic pituitary adenoma and in occult tumours [48,69,[82][83][84]. A recent review reported a prevalence of 26% of EAS in patients with cyclic Cushing's syndrome from published series and case reports [83].…”
Section: Specific Considerations In Easmentioning
confidence: 95%
“…Neuroendocrine tumors of the thymus are the most frequently represented, followed by neuroendocrine bronchial tumors [4, 1926]. Other tumors reported as responsible of cyclic ectopic CS are pancreatic, renal and gastric NET [2729], epithelial thymoma [30], phaeochromocytoma [31], carotid glomus tumor [32] and ectopic pituitary adenoma [33]. Surprisingly, although small cell lung carcinoma is frequent in patients with ectopic CS, biochemical episodes of cycling seem to be rare.…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnosis includes cyclic Cushing's, characterized by periodic fluctuations of cortisol secretion. Cycles of hypercortisolism alternate with phases of normal or low cortisol production, which can last days or years (17). It can be present in ACTH dependent or independent Cushing's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…It can be present in ACTH dependent or independent Cushing's syndrome. Approximately in 10% of cases an adrenal tumor is the underlying cause (17). In this case, although there was a paradoxical increase of cortisol with a 100% rise in 24 h UFC during the Liddle's test suggestive of PPNAD, basal urine free cortisol levels were within normal values.…”
Section: Discussionmentioning
confidence: 99%